Epicardial adipose tissue is associated with the formation of left ventricular aneurysm after myocardial infarction. (25th November 2020) - Yang, C.D; Shen, Y; Zhang, R.Y; Lu, L; Ding, F.H; Yang, Z.K; Hu, J; Shen, W.F; Wang, X.Q
Abstract: Background: Left ventricular aneurysm (LVA), a serious complication of transmural myocardial infarction, is generally related to poor cardiovascular outcomes. The formation of LVA is essentially an inflammatory remodeling process regulated by multiple systemic and local factors. Epicardial adipose tissue (EAT), a depot of visceral adipose tissue directly overlying the myocardium, is increasingly recognized as an important immune organ by secreting a variety of bioactive adipocytokines. However, the relation of EAT to the development of LVA is still unclear. Purpose: In this study, we sought to investigate the association between EAT volume and the formation of LVA in subjects with previous myocardial infarction (MI). Methods: A total of 55 subjects with previous MI and the presence of LVA, and age- and sex-matched 50 subjects with previous MI but without LVA were enrolled between October 2011 and June 2019. EAT was quantified and the presence of LVA was ascertained by cardiac magnetic resonance (CMR). EAT volume was indexed to body surface area. Results: In the overall population, EAT volume index was correlated positively to log-transformed N-terminal pro-brain natriuretic peptide (NT-proBNP) levels (Pearson's r=0.332, P=0.002), and inversely to left ventricular ejection fraction (LVEF; Pearson's r=−0.240, P=0.031). The indexed EAT volume was significantly higher in subjects with than without LVA (41.10±11.73 vs. 33.25/11.70 mL/m 2, P=0.003). In subjects with LVA, EAT volume index was further increased in those at older age (43.59±13.09 mL/m 2 vs. 37.29±8.26 mL/m 2, P=0.029) or with type 2 diabetes (43.38±12.32 mL/m 2 vs. 35.20±7.67 mL/m 2, P=0.013). After adjusting for sex, age and the presence of diabetes in the multivariate analysis, tertiles of EAT volume index remained significantly associated with the presence of LVA (P for trend=0. 003). Strikingly, compared to the lowest tertile (≤30.80 mL/m 2 ), the intermediate (30.80–44.13 mL/m 2 ) and highest (>44.13 mL/m 2 ) tertiles of EAT volume index corresponded to 4.869– (95% CI 1.792–14.155, P=0.003) and 4.876– (95% CI, 1.787–14.206, P=0.003) increased risk for LVA. Conclusion: Our study suggests that EAT volume is independently associated with the formation of LVA and reduced cardiac function after myocardial infarction. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Natural Science Foundation of China